Present Tense - Lebbeus Woods (Oz, 1990)
Memory conceived as a recollection of things past serves the idea of tradition as the basis of human culture. Yet as a culture depends less on tradition and more on its own inner dynamics for its evolution, the concept of memory undergoes a transformation.